Analisis Usaha Industri Makanan Pancake Durian Di Kota Pekanbaru Pada Masa Sebelum dan Pada Saat Pendemi Covid-19 (Studi Kasus: Mega Rasa Pekanbaru) - Vivin Pratiwi (JIP ( Jurnal Industri dan Perkotaan ), 2022)
This study aims to determine the profits and business efficiency of the Mega Rasa durian pancake food industry in Pekanbaru City before and during the COVID-19 pandemic. Determination of the sample This study uses purposive sampling. The sample used is the durian pancake industry Mega Rasa Pekanbaru. This study uses the t-test analysis method using the SPSS (Statistical Product And Service Solutions) program. The results showed that the average profit of the Mega Rasa durian pancake business in Pekanbaru City in the pre-covid-19 period was Rp. 10,439,750 with an efficiency of 1.417636872 and during the covid-19 pandemic the average profit was Rp. 7,040,667 with an efficiency of 1.343791801. Judging from the results of the t-test of 7.012 and alpha of 0.05 and significant (2-tailed) of 0.00, which indicates that the significant value (2-tailed) < alpha (0.05), means that H0 is rejected, Ha is accepted. which means that there is a real difference between the profits of the Mega Rasa durian pancake business in Pekanbaru City in the pre-covid period and during the covid-19 pandemic.